Are Glycaemic Response, Glycaemic Index, and Glycaemic Load of Traditional Palm Sugar (Arenga pinnata) Different from Cane Sugar?: An Oral Glucose Tolerance Test - A'immatul Fauziyah; Sofia Wardhani; Luh Desi Puspareni (Amerta Nutrition, 2022)
Background: Palm sugar (Arenga pinnata) is believed to benefit people with diabetes mellitus since they believe it has a low glycemic index. However, the total carbohydrates in palm sugar, particularly sucrose, are high. Thus, offering palm sugar to diabetic people still needs further studies. Objectives: The purpose of this study was to examine differences in the glycemic response, glycemic index, and glycemic load of palm sugar compared to cane sugar. Methods: This study used an experimental design. Measurement of the oral glucose tolerance test (OGTT) through the finger-prick capillary blood test method. The main materials in this study were commercial white cane sugar as reference food and traditional palm sugar product of Lebak District, Banten Province, as a test food. Reference food and test food were provided equivalent to 50 g available carbohydrate dissolved in 250 ml mineral water subjected to 5 men and 5 women. The glycemic response was determined by the area under the curve (AUC) of the trapezoid method. The difference in glycemic response between the reference food and the test food was assessed using the independent sample t-test. Results: The peak of the increase in blood glucose occurred at 30 minutes. There was no difference in glycemic response between the reference food and the test food (p-value 0.685). The palm sugar glycemic index was 98.71 and was categorized into the high glycemic index category. Meanwhile, the glycemic load of palm sugar and cane sugar was 11.80 and 12.22, those categorized into the medium glycemic load category. Conclusions: No differences in glycemic response between palm sugar and cane sugar. The glycemic index of palm sugar was considered high and was not different from cane sugar. The glycemic load of palm sugar and cane sugar was classified as moderate due to the small serving size. Using palm sugar less than cane sugar was expected to provide a lower glycemic response, glycemic index, and glycemic load.